2013
DOI: 10.1016/j.ejphar.2013.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal calcium dysregulation at the nexus of diabetes and brain aging

Abstract: Accumulating evidence is associating disorders of lipid and glucose metabolism, including the overlapping conditions of insulin resistance/metabolic syndrome, obesity and diabetes, with moderate cognitive impairment in normal aging and elevated risk of Alzheimer’s disease. It appears that a common feature of these conditions is deficient insulin signaling, likely affecting the brain as well as canonical peripheral target tissues. A number of studies have documented that insulin directly affects brain processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 193 publications
(225 reference statements)
1
26
0
Order By: Relevance
“…The mildly impaired object recognition memory we observed is consistent with the calcium hypothesis of brain aging, which holds that “sustained disruption of mechanisms that normally regulate intracellular Ca 2+ signaling is pivotal for triggering adverse changes in the functioning of neurons”47. Sustained Ca 2+ dysregulation in neurons has also been implicated in the cognitive decline associated with obesity, diabetes, insulin resistance/metabolic syndrome, and Alzheimer disease484950. Additional studies are needed to fully characterize the mechanistic relationships that link nBMP2 with hippocampal LTP, but the evidence so far is consistent with our hypothesis that absence of nBMP2 from the nucleus leads to dysregulation of intracellular Ca 2+ signaling.…”
Section: Discussionsupporting
confidence: 62%
“…The mildly impaired object recognition memory we observed is consistent with the calcium hypothesis of brain aging, which holds that “sustained disruption of mechanisms that normally regulate intracellular Ca 2+ signaling is pivotal for triggering adverse changes in the functioning of neurons”47. Sustained Ca 2+ dysregulation in neurons has also been implicated in the cognitive decline associated with obesity, diabetes, insulin resistance/metabolic syndrome, and Alzheimer disease484950. Additional studies are needed to fully characterize the mechanistic relationships that link nBMP2 with hippocampal LTP, but the evidence so far is consistent with our hypothesis that absence of nBMP2 from the nucleus leads to dysregulation of intracellular Ca 2+ signaling.…”
Section: Discussionsupporting
confidence: 62%
“…Impaired cerebral glucose utilization in the prefrontal cortex is inversely associated with body mass index in human subjects (Volkow et al, 2009), suggesting an adverse effect of a chronic positive energy balance on neuronal bioenergetics. Rats or mice maintained on high-fat and/or high-sugar diets, and diabetic animals, exhibit many of the cellular and molecular hallmarks of brain aging including oxidative damage (Elahi et al, 2016), neuroinflammation (Jayaraman et al, 2014), impaired neuronal Ca 2+ homeostasis (Thibault et al, 2013), impaired autophagy (Li et al, 2017), and dysregulation of neuronal network activity (Margineanu et al, 1998). Insulin-resistant mice exhibit impaired hippocampal neurogenesis, which is associated with oxidative stress, inflammation, and impaired hippocampus-dependent spatial learning and memory (Lindqvist et al, 2006; Stranahan et al, 2008a; Gurung et al, 2016).…”
Section: Metabolic Factors Can Accelerate or Decelerate Brain Agingmentioning
confidence: 99%
“…In vitro experiments have shown synaptic facilitation in PFC pyramidal neurons (Hempel et al, 2000;Wang et al 2006). Several other studies have shown age-related changes in synaptic plasticity (not modeled here), some correlating these changes with learning and memory deficits (Norris et al, 1998a(Norris et al, , 1998bBach et al, 1999;Rosenzweig and Barnes, 2003;Thibault et al, 2007;Gant et al, 2011;Thibault et al, 2013;Gant et al, 2014;Gant et al, 2015).…”
Section: Discussionmentioning
confidence: 63%